Fault Segmentation Pattern Controlled by Thickness of Brittle Crust. Issue 19 (1st October 2021) - Jiao, L.; Klinger, Y.; Scholtès, L.
Abstract: During large earthquakes, seismic sources tend to split in several sub‐events that rupture neighboring fault patches called fault segments. The scaling of such segmentation plays a decisive role in earthquake rupture dynamics, especially for strike‐slip events. Using numerical modeling we demonstrate that when a pristine layer of brittle material is sheared, the first oblique Riedel fractures nucleate with a regular spacing that is controlled by the thickness of that layer. During later localization of the deformation, those initial fractures control the spatial structuration of the entire fault system. Analyzing the horizontal stress distribution in fault‐parallel direction for different ratios between inter‐Riedel distance and material thickness, we identify a threshold at 1.5, beyond which the stress switches from compressional to tensional and leads to the nucleation of a new Riedel fracture. Thus, the inter‐Riedel segment length appears to be controlled by the vertical distribution of stress along the fault. Plain Language Summary: Geologic faults, including strike‐slip faults, are not continuous smooth structures. Detailed fault mapping and earthquake rupture traces show that they are rather formed by discontinuous segments bounded by jogs and bends. The structure of faults impacts the way a rupture propagates during an earthquake, and eventually where the earthquake rupture starts and stops. Although such spatial organization as long been noted from natural observations and analogue experiments, the physical processes presiding at such organization remain elusive. In this work, we use numerical experiments to show that the fracture pattern is primarily controlled by the thickness of the brittle part of the crust of the Earth and that there is a critical ratio between inter‐fracture distance and thickness for which the system is stable and does not need to rupture to accommodate shear. The value, ∼1.5, of this ratio is found to be the same in our numerical models, in analogue experiments, and for real earthquake ruptures, pointing to a universal physical process. Key Points: Shear fractures, including earthquake ruptures, are spatially segmented following a pattern inherited from early fracture development Numerical simulations show both upward and downward crack propagation when a brittle layer is subjected to strike slip faulting Fault segmentation is spatially organized to maintain material in a stable compressive state of stress through localized tensile ruptures